Effect of fermented bee pollen on metabolic syndrome in high-fat diet-induced mice - Sha Yan; Kai Wang; Xiaoying Wang; Aiqun Ou; Feiran Wang; Liming Wu; Xiaofeng Xue (Food Science and Human Wellness)
Bee pollen has potential in preventing metabolic syndrome (MetS). The present study aimed to investigate the effect of yeast-fermented wall-broken bee pollen (YB) intervention on ICR mice with MetS induced with a high-fat (HF) diet. After YB intervention in mice for 16 weeks, the effect on alleviating MetS was evaluated based on MetS serum parameters, hepatic oxidant status markers and gut microbial populations. The results of animal experiment showed that YB intervention attenuated MetS. Based on multivariate statistical analysis results, YB treatment significantly increased glutathione S-transferase (GST) and catalase (CAT) activities and decreased the malondialdehyde (MDA) level in the liver. Further investigation showed that YB restored the Nrf-2-Keap-1 pathway to alleviate oxidative stress. Additionally, gut microbial community analysis revealed that YB restored the increase in the Firmicutes to Bacteroidetes (F/B) ratio (6.94 for the HF group and 3.74 for HF + YB group) and improved Lactobacillus and Lactococcus abundance induced by the HF diet. Overall, YB improved function and prevented MetS by modulating the gut microbiota and alleviating oxidative stress.